Tribological properties of grease containing graphene oxide or hexagonal boron nitride - Igor Jakub Dąbrowski; Krzysztof Gocman; Tadeusz Kałdoński (Biuletyn Wojskowej Akademii Technicznej, 2019)
The purpose of this paper is to present the results of research of tribological behavior of basic greases (of 2. NLGI class) including different mass concentration concentration (0.05%, 0.1%, 0.2%, 0.5%, 1%, 2%) of additives: graphene oxide (produced by the Institute of Electronic Materials Technology, Warsaw) and hexagonal boron nitride (produced by the Military University of Technology, Warsaw). In the first part of this publication there is elementary information about graphene and its applications, especially in tribological field. The next part of the paper contains the results of research on the mentioned above samples, which were investigated with four-ball apparatus T-02 and Universal Micro/Nano Tester UNMT (CETR, CA, USA), at the Department of Tribology and Service Fluids Logistics at the Faculty of Mechanical Engineering, Military University of Technology. The results proved a positive effect of adding graphene oxide or hexagonal boron nitride to basic grease on its tribological properties. In case of “water dispersion of graphene oxide”, its tribological properties were similar to the samples including significant concentration of GO. Keywords: graphene, grease, graphene oxide, hexagonal boron nitride